REASONS OF AVERSION TO FOOD AT CHILDREN OF EARLY AGE: DIFFERENTIAL AND DIAGNOSTIC SEARCH AND CORRECTION WAYS - О. N. Komarova; А. I. Khavkin (Вопросы современной педиатрии, 2014)
Aversion to food is observed at children at different stages of their development since the neonatality period. This state can be caused by several reasons. First, by coexisting diseases among which there are pathology of a gastrointestinal path (gastroesophageal reflux disease, malabsorption syndrome), neurologic (damage at ischemia or hemorrhage of a brain axis and cervical cord, neuromuscular diseases) and logopedic pathology (ankyloglossia), metabolic diseases (organic aciduria) and food intolerance. Secondly, disorder of eating behaviour can be connected with organic pathology, for example with gullet and stomach developmental malformations (esophageal achalasi, short gullet, pyloristenosis), congenital pathology of cardiovascular system, respiratory organs, liver. Thirdly, aversion to food can take place against complete health without visible objective reasons and, as a rule, is interfaced to the wrong feeding. For this reason the determination of possible reasons of eating disorder is fundamental for the achievement of clinical effect. However, besides treatment of the main disease the complex behavioural and nutritional correction which is considered in this article is justified for all patients with aversion to food.